Ethical vs. non-ethical - is there a difference? Analyzing performance of ethical and non-ethical investment fund - Linnéa Lundberg; Jiří Novák; Maria Vikman (Charles University in Prague, Institute of Economic Studies (IES), 2009)
Ethical investments have become increasingly popular over the past years. Ethical funds restrict their investment based on environmental, social and/or ethical criteria. Prior research on the performance of ethical versus non-ethical funds yields mixed results. This paper investigates the differences in risk profiles and realized returns between ethical and non-ethical funds. A sample of 23 ethical funds and 152 non-ethical funds covering the time period between 2000 and 2007 is investigated. The analysis of the portfolio composition shows that there are small differences in the structure of portfolios concerning industry composition and company size. However, the ethical funds tend to hold more stocks in their portfolios than non-ethical ones. The results provide some evidence on the underperformance of ethical funds; this underperformance is stronger in years of poor stock market performance, which indicates that systematic risk of ethical funds may be higher.
Keywords: G12; C21; 330; ethical; social responsible investment; SRI; investment; funds; portfolio; returns; risk; screening; Sweden; Investmentfonds; Nachhaltige Kapitalanlage; Kapitaleinkommen; Risiko; Schweden